Lord and Lady Bunny -- almost royalty! - Horvath, Polly; Blackall, Sophie (New York Schwartz & Wade Books, 2014)
"Madeleine and her hippie parents travel to England to run a candy shop. Meanwhile Mr. and Mrs. Bunny also travel to England, where Mrs. Bunny tries to weasel her way into the ranks of royalty"--
"translated from the Rabbit" on cover.
750L
101285
Keywords: Human-animal communication; Hippies; Rabbits; Voyages and travels; Kings, queens, rulers, etc; England; Juvenile works - Fiction